LITERATUR REVIEW : PEMENUHAN HAK PENDIDIKAN BAGI ANAK-ANAK DISABILITAS - Ananda Lufi Nabila; Hastin Trustisari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
. Human Rights (HAM) include the right to education for every individual, including children with disabilities. The importance of inclusive and quality education for children with disabilities, in accordance with human rights principles which include integrity, freedom and equality. This research method uses a descriptive literature review method. Conclusion With appropriate and inclusive education, children with disabilities can develop the skills necessary to live independently and participate actively in society. They will also be better prepared to compete in the world of work, opening up better career opportunities and improving the overall quality of life. Suggestions in this case can be given to provide educational rights for children with disabilities which require real attention and action from the government and public awareness.